Volatile Organic Compounds (VOCs) Removal from Indoor Air by Heterostructures/Composites/Doped Photocatalysts: A Mini-Review - Enesca, Alexandru; Cazan, Cristina (Nanomaterials, 2020)
The impact of volatile organic compounds (VOCs) on indoor air quality and, furthermore, on human health is still a subject of research investigations considering the large increase in forms of cancer and related diseases. VOCs can be 10 times higher in indoor air concentrations then that of the outdoors, as a consequence of emissions from electronics, building materials and consumer goods. Direct transformation of VOCs in mineralization products seems to be an alternative to reduce indoor air contaminants. The advantage of photocatalysis implementation in indoor air treatment is given by the absence of additional chemicals (such as H2O2) and waste. The present mini-review presents a comparative study on VOCs photocatalytic removal considering the photocatalyst composition, morphology and specific surface. The sheet-like morphology seems to provide a higher number of active sites which may contribute to oxidative reactions. The insertion of materials able to increase light absorbance or to mediate the charge carrier’s transport will have a beneficial impact on the overall photocatalytic efficiency. Additionally, surface chemistry must be considered when developing photocatalysts for certain gas pollutants in order to favor molecule absorbance in the interfacial region. An energy consumption perspective is given based on the light intensity and irradiation period.
Keywords: : photocatalysis; heterostructures; composites; indoor air; volatile organic compounds